Vaccine-associated paralytic poliomyelitis in a child: fast transformation from Sabin-like virus to vaccine-derived poliovirus triggered an epidemiological response in two countries of the European region - Olga E. Ivanova; Liubov I. Kozlovskaya; Tatiana P. Eremeeva; Armen K. Shakaryan; Alexander P. Ivanov; Olga Y. Baykova; Alexander Y. Krasota; Elena Y. Shustova; Aida N. Mustafina; Nadezhda S. Morozova; Makhtob S. Bobokhonova; Sergei E. Deshevoi; et al. (International Journal of Infectious Diseases, 2022)
Objectives: The detection of a vaccine-derived poliovirus (VDPV) requires an epidemiological assessment and response. Using repeated stool sampling from a child who is immunocompetent and was vaccinated against poliomyelitis with acute flaccid paralysis, a case of an extremely rapid evolution of Sabin-like poliovirus (PV) type 3 was traced in the child's body. Methods: The case was independently identified in two countries—Tajikistan and Russia. Stool samples for the study were also independently collected in two countries on different days from the onset of paralysis. Virological, serological, and molecular methods; full genome Sanger; and high-throughput sequencing were performed to characterize isolates. Results: PV isolates from samples collected on days 2, 3, and 14 contained eight, seven, and seven mutations in the VP1-coding region, respectively, and were classified as Sabin-like PV type 3. The isolates from samples collected on days 15 and 18 had 11 mutations and were classified as vaccine-derived PVs, which required an epidemiological response in the two countries. Conclusion: The results indicate the need to continue acute flaccid paralysis surveillance, maintain high vaccination coverage, and develop and introduce new effective, genetically stable PV vaccines.